RAMAN CHARACTERIZATION OF CuCr2-xSnxS4 SPINELS - Valencia-Gálvez, P.; Peña, O.; Moris, S.; Barahona, P. (Journal of the Chilean Chemical Society, 2019)
Polycrystalline thiospinels CuCr2-xSnxS4 (x = 0.4, 0.8, 1.0 and 1.4) were synthesized via conventional solid-state reaction. The samples were characterized by powder X-ray diffraction (XRD), energy-dispersive X-ray analysis (SEM-EDS) and Raman spectroscopy. All the samples were indexed in the space group . The Raman spectra confirmed the structure of normal spinel type with five characteristic signals for the active modes in Raman. Magnetic measurements, performed for the phases with x = 0.8 and 1.0, showed irreversible antiferromagnetism with dominant ferromagnetism and spin glass behavior.